Synergetic HepG2 cells suppression efficacy of Tripterygium wilfordii and Scutellaria barbata through EGFR/PI3K/Akt pathway - Susu Liu; Yuan Liu; Luanying He; Fei He; Na Wang; Jinting Peng; Changyuan Yu; Shihui Wang (Elsevier, 2022)
Traditional Chinese medicines (TCMs) Tripterygium wilfordii Hook. f. (TW) and Scutellaria barbata D. Don (SB) are reported to have anticancer activity. However, the synergetic anti-liver cancer efficacy is still unknown. Herein, we demonstrated that the combination of TW and fermentation product of SB by yeast (TW+SB) could markedly improve the HepG2 cell suppression capacity as compared to individual TW or SB. Hence, synergetic mechanisms of TW+SB combination were further investigated by systems pharmacology, LC-MS, etc. The results showed that fermentation increases the concentration of active components of SB rather than those of TW, leading to the increase of HepG2 cell inhibition efficacy of SB. TW+SB combination effectively suppresses proliferation, migration, and invasion of liver cancer cells by inducing EGFR/PI3K/Akt signaling pathway mediated apoptosis. In conclusion, TW+SB combination showed outstanding synergetic anti-liver cancer effect, and it might offer a promising treatment option for cancer patients.